Junie b. jones collection, books 9-12 eaudiobook - Park, Barbara (Junie B. Jones, 2006)
The world's funniest kindergartner is back with four more silly escapades in one audiobook. Junie B. Jones Is Not a Crook Someone has taken Junie B.'s new black furry mittens! And they kept them! So when Junie B. finds a wonderful pen, she should be allowed to keep it, too. Right? Junie B. Jones Is a Party Animal Lucille is having a slumber party at her nanna's big giant house! For Grace and Junie B., sleeping at nanna's is a dream come true! What could possibly go wrong? Juine B. Jones Is a Beauty Shop Guy Is Junie B. on her way to a great new career as a beauty shop guy? Or is she about to have the worst hair day ever? Junie B. Jones Smells Something Fishy It's pet day at school. No dogs allowed! And that's the only kind of pet Junie B. has. SHe'll just have to find a new pet. Like maybe a jar of ants. Or a wiggly worm. Or—could it be—something even better?